Notary Legal Protection Against Crime In The Case That Called As Witnesses Or Suspect - Novi Ahmad Arifin; Roswati Dewi; Ngadino Ngadino (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study were 1) to identify and explain the legal protection of the notaries who was called as a witness or a suspect in the Process of Investigation and Prosecution Pre. 2) To determine the constraints in the implementation of legal protection against notaries who were called as witnesses or suspects.This research using normative juridical approach. Normative approach research problems in terms of its legislation. Methods normative constitute legal research done by examining the data or materials library that is secondary data in the form of legislation, a wide range of literature and Internet sources that are supported by field research is the primary data, which analyzes the rules relating to the Notary Public.Based on data analysis concluded that: 1. Notaries are obliged to keep confidential all matters communicated to him in his capacity as a notary, even though there are some that are not listed in the deed, and has been considered to represent themselves notary in a trial that deed, made by or in the presence of a notary public is an evidence that has the strength of evidence Perfect. 2. Notary criminal cannot be held accountable when there is a loss to either party as a result of the false documents of one of the parties, as Notary simply record what is conveyed by the parties to be poured into the deed. False information submitted by the parties is the responsibility of the parties.Keywords: Notary Act (UUJN); Notarization; Notary Liability.